Review Review of National Economic Recovery Program in Indonesia - Angling Nugroho Kemenangan; Lisno Setiawan (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2021)
The escalation of Covid-19 and the sharp economic slowdown and tremendous disruption in various aspects of life, especially health, social, economic and financial impacts must be mitigated on the public welfare through extraordinary policies. The Covid-19 response and economic recovery program is an extremely important program designed in an atmosphere of emergency / urgency. Speed ​​is very important, but on the other hand, accountability, transparency and good governance principles should not be ignored. In the midst of an emergency situation in handling Covid-19, especially the PEN program, many government programs in their implementation require very fast, urgent and massive handling, which of course must be followed by strengthening good governance, through the application of the principles of prudence, accountability and transparency. The results of the review show that in the implementation of the PEN program there are problems with regulations, budget, data, coordination and technical implementation, monitoring and evaluation, and information technology. These constraints are related to one another. Based on references to evaluations of governments, institutions, and best practices in countries that have successfully implemented the program, the authors present solutions related to these problems.